Effect of different corrosion inhibitors on the corrosion of cast iron in palm biodiesel - Fazal, M.A.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (2011)
Biodiesel is currently in regular use as an alternative fuel over conventional petroleum diesel. However, corrosion of automotive materials is one of the concerns related to biodiesel compatibility issues. In addition, auto-oxidation of biodiesel can also enhance the corrosiveness of biodiesel. The present study aims to investigate inhibition effect of ethylenediamine (EDA), n-butylamine (nBA), tert-butylamine (TBA) against corrosion of cast iron. Static immersion tests in biodiesel in the presence (100 ppm) and absence of different corrosion inhibitors were carried out at room temperature for 1200 hours. At the end of the test, corrosion characteristic was investigated by weight loss measurements and changes on the exposed metal surface. Fuels were analyzed by using TAN (total acid number) analyzer and FTIR in order to investigate the acid concentration and compositional characteristics respectively. Surface morphology was examined by digital photography and scanning electron microscope (SEM). Oxide layers were investigated by X-ray diffraction. Results showed that TBA was more effective corrosion inhibitor in reducing corrosion than others. (C) 2011 Elsevier B.V. All rights reserved.